Performative Experience Design - Spence, Jocelyn; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents a novel framework for understanding and designing performative experiences with digital technologies. It introduces readers to performance theory and practice in the context of HCI and gives a practical and holistic approach for understanding complex interactions with digital technologies at the far end of third-wave HCI. The author presents a step-by-step explanation of the Performative Experience Design methodology, along with a detailed case study of the design process as it was applied to co-located digital photo sharing. Finally, the text offers guidelines for design and a vision of how PED can contribute to an ethical, critical, exploratory, and humane understanding of the ways that we engage meaningfully with digital technology. Researchers, students and practitioners working in this important and evolving field will find this state-of-the-art book a valuable addition to their reading.
Preface -- Introducing Performative Experience Design -- Performativity -- What Exactly is Performance? -- The Performative Experience Design Methodology -- Designing Collect Yourselves! -- Performing Collect Yourselves! -- Guidelines for Designers/Researchers -- Looking Forwards.-Index.
Keywords: Computer science; User interfaces (Computer systems).; Graphic design; Computer Science; User Interfaces and Human Computer Interaction; Interaction Design; Electronic books